Exploring transformative and multifunctional potential of MXenes in 2D materials for next-generation technology - Mishra, Raghvendra Kumar; Sarkar, Jayati; Verma, Kartikey; Chianella, Iva; Goel, Saurav; Nezha, Hamed Yazdani (Elsevier, 2024)
MXenes, a rapidly growing family of two-dimensional (2D) transition metal carbides, nitrides, or carbonitrides (Mn+1XnTx, where M is a transition metal, X is carbon, nitrogen, or both, and T represents surface functional groups), have captured the scientific community's interest due to their exceptional physicochemical properties and diverse technological applications. This comprehensive review explores the latest breakthroughs in MXene synthesis and characterisation, emphasising their multifaceted applications in energy storage, catalysis, sensing, and other cutting-edge domains. This review examines the most widely used MXene synthesis strategies, including selective etching and delamination, and highlight recent advancements in controlling surface terminations, composition, and morphology. The influence of these synthetic parameters on MXene properties is discussed in detail. Characterisation techniques, ranging from spectroscopic methods to electron microscopy, are essential for elucidating MXenes' structure-property relationships. Research into energy storage leverages MXenes' high electrical conductivity, large surface area, and chemical tunability. This has led to significant progress in the field. This paper presents research efforts focused on optimising MXenes for both battery and supercapacitor applications. Additionally, the catalytic prowess of MXenes, particularly in electrocatalysis and photocatalysis, is explored, emphasising their role in green energy technologies and environmental remediation. MXenes' remarkable sensitivity and selectivity make them promising candidates for sensing various gases, biomolecules, and ions, offering exciting possibilities in healthcare and environmental monitoring. Importantly, this review underscores the need for continued optimisation of MXene synthesis protocols to achieve large-scale production, enhanced stability, and precise control over properties across various fields.
Keywords: MXenes; 2D materials; Synthesis of MXenes; Characteristics of MXenes; Applications of MXenes